Simulation on polytropic process of air springs. Issue 7 (3rd October 2016) - Li, Xuebing; Wei, Yintao; He, Yuan
Abstract : Purpose: The purpose of this paper is to propose a method to simulate the polytropic process of air springs. Design/methodology/approach: An iterative finite element method (FEM) is proposed. Findings: The proposed method is reliable and effective in solving the polytropic process of air springs. Originality/value: This work would be helpful for understanding the simulation of pneumatic structures, and the proposed modified FEM would be useful for improving the simulation of the mechanical behavior of an air spring.